Mass Spectrometry Application in Biology (MDPI - Multidisciplinary Digital Publishing Institute, 2014)
Mass spectrometry (MS) has become a vital tool for scientist in exploring how biological systems function and how therapeutic drug intervention (both small molecules and biologics) impact these systems. The application of mass spectrometry has advanced our knowledge in the biological sciences through the study of proteins and peptides in proteomics and as biomarkers, imaging via MALDI MS, and analysis of SNP's in the genome to allow personalized medical treatment. The aim of this book is to provide a glimpse of some of the many applications of the advancing field of mass spectrometry and its application to complex biological problems. The topics presented here touch on many of the areas listed above will hopefully serve as a catalyst to generate new ideas for the continued innovative application of mass spectrometry to the fields of medicine, biology and beyond.